2001
DOI: 10.1017/s0950268801005398
|View full text |Cite
|
Sign up to set email alerts
|

The seroepidemiology of varicella in Italy

Abstract: We conducted a seroepidemiological study to evaluate the potential impact of mass varicella vaccination on the transmission of varicella-zoster virus (VZV) in Italy, where vaccination is not mandatory. We tested 3179 serum samples, collected from September 1996 to October 1997, for specific anti-VZV antibodies using a commercially available ELISA. The results confirmed that varicella typically involves children (82.1% seroprevalence among 10- to 14-year-olds) and that the mean age of acquiring the infection se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 21 publications
11
41
4
Order By: Relevance
“…3). 16,17 More in detail, seroprevalence observed in the present study was significantly greater in comparison to the ones previously observed in the age classes from 1 to 15-19 y of age. Starting from the 20-39 age class, no statistically significant differences were detected among the 3 studies.…”
Section: Resultscontrasting
confidence: 62%
“…3). 16,17 More in detail, seroprevalence observed in the present study was significantly greater in comparison to the ones previously observed in the age classes from 1 to 15-19 y of age. Starting from the 20-39 age class, no statistically significant differences were detected among the 3 studies.…”
Section: Resultscontrasting
confidence: 62%
“…A Turkish study reported a VZV seroprevalence of 90% in 15 to 19-year olds only [24]. A recent Italian study based on more than 3,000 sera from 18 regions (both North and South Italy) indicated that VZV seroprevalence only reaches 91.8% for the 20 to 39-year olds [12]. This study reported that about 17% of Italian 10 to 19-year olds lacks immunity to VZV.…”
Section: Discussionmentioning
confidence: 49%
“…In Italy, as in other countries in the northern hemisphere, varicella is an endemic infection with a striking seasonal pattern and a peak incidence in winter and spring. A study comparing the few available Italian epidemiological data over time showed that the percentage of varicella cases noted in the 15-year age group increased from 6.0% in 1961-1970 to 17.7% in 1991-1996 [16] . The percentage of females of reproductive age who have no specific anti-VZV antibodies is 17.2% among the 15-to 19-year age group, and 9.2% among the 20-to 39-year age group.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of females of reproductive age who have no specific anti-VZV antibodies is 17.2% among the 15-to 19-year age group, and 9.2% among the 20-to 39-year age group. Hence, the Italian data suggest that the risk of acquiring varicella during pregnancy is increasing [16] . In contrast to this, and to several studies in the US and UK, no such indication emerged from the German epidemiological data over the period from 1987 to 1998 [6 ; Enders et al, 1998, unpublished data].…”
Section: Discussionmentioning
confidence: 99%